Percutaneous Snaring and Retrieval of Cephalad Migrated Double J Stents in Pediatric Patients—A Bailout Technique Urologists Should Know - Khanak K. Nandolia; Udit Chauhan (Annals of the National Academy of Medical Sciences (India), 2023)
Double J (DJ) stents are placed in patients with obstructive uropathy to relieve the obstruction. Curved ends prevent slippage or migration of the stent. Antegrade migration into the urinary bladder or retrograde migration into the ureter are common complications. Mode of retrieval of migrated stents depends upon the location of the stent. We present a case series of four cases with percutaneous snaring of cephalad migrated DJ stents in pediatric patients.